Braincase redescription of Efraasia minor Huene, 1908 (Dinosauria: Sauropodomorpha) from the Late Triassic of Germany, with comments on the evolution of the sauropodomorph braincase. Issue 1 (30th August 2017) - Bronzati, Mario; Rauhut, Oliver W M
Abstract: The braincase anatomy of the sauropodomorph dinosaur Efraasia minor (Late Triassic, Norian, Löwenstein Formation of Germany) is redescribed in detail, adding new information based on CT scan data. We discuss the evolution of sauropodomorph braincases from a phylogenetic perspective, focusing on non-neosauropodan representatives. For this, we revised braincase characters used in data matrices focused on this assemblage of taxa. This led to the recognition of problems with some of the phylogenetic characters, especially regarding the basal tubera complex, which did not accurately reflect the morphological variation observed among taxa within the group. We also discuss previous misidentifications of the soft tissues associated with the presence of a divided metotic foramen among sauropodomorphs. This has implications for the recognition of the structures associated with braincase foramina in non-sauropodan sauropodomorphs, and we propose that the path for the jugular vein was either through the posterior foramen resulting from this division or through the foramen magnum. Finally, our study demonstrates a series of differences regarding braincase anatomy between non-sauropodan and sauropod taxa. However, it remains unclear if these differences might be due to a drastic morphological change or if they simply reflect the small number of braincase materials of non-neosauropodan sauropods, which might indicate a more stepwise evolution.